Fatigue Damage Characteristics of Offshore Wind Power Large-Diameter Monopile Structures During Driving Process - Tao CHEN; Ruilin DING; Wei GUO; Junhui SHE; Weichao LI (南方能源建设)
[Objective] Large-diameter monopile foundations are widely used in marine engineering in China and are typically installed through penetration. Due to the impact of the pile hammer, the pile body experiences continuous impact loads during the driving process, making it susceptible to fatigue issues. Therefore, it is particularly important to study the penetration process and fatigue damage of large-diameter monopile. [Method] This paper focused on the large-diameter monopile foundations. Based on the engineering field test data, a segmented pre-setting modeling method was proposed to address the issue of excessive computational workload in continuous pile penetration, allowing for segmented calculations of the monopile driving process. The feasibility of this method in calculating the mechanical response of the pile body during driving was verified. Time-history responses of displacement, velocity and stress at target points on the monopile under a single driving action were obtained. Fatigue damage at the welded position of the monopile varying cross-sections was calculated using the S-N curve and Palmgren-Miner theory. [Result] The results show that the proposed segmented pre-setting modeling method effectively reflects the mechanical response of the pile body under driving action. The trends of displacement, velocity and stress are in good agreement with the measured data. The error between the simulated maximum stress value and the measured value is within 10%. [Conclusion] The damage to the target cross-section of the monopile caused by a single driving action is directly related to the effective driving energy received. After 1017 hammer strikes, the fatigue damage at the welding position of the monopile varying cross-sections is 7.578%, accounting for 22.734% of the fatigue life under the designed safety premise. Therefore, attention should be paid to the fatigue damage of the pile body caused by the driving during the penetration process.